Cholera Case Study on Broiler Poultry Collected from Communities Farm in Banda Aceh Using Pathology Method - Zainuddin Z (Universitas Syiah Kuala, 2014)
Fowl cholera is an infectious bacterial disease that is widespread in poultry in the world caused by Pasteurellamultocida. The disease infects both fowl and wild poultry. Poultry become more sensitive to the disease on advance age of chicken and on laying chicken. Generally, thisdisease infects breeding flocks of males with the aged of 33 weeks, and in breeding flocks at age 35 weeks with the symptoms of increasedmortality, and wattle and leg swelling. P multocida infection in chickens aged 25 weeks was reported in Korea. In northern Iran, cholera hasbeen reported endemic in poultry breeders. In chickens, this disease can be manifested in the acute and chronic forms. Generally, fowl cholera isasepticemic disease characterized by high morbidity and mortality rates, usually runs an acute, but in an endemic area the poultry is lesssensitive to this disease, thus,it was grouped to chronic disease. Chronic form of fowl cholera may occur after the outbreak. Recently, fowlcholera incidence in broiler chickens is becoming more common. These cases are associated with farm conditions that are very unhygienic andthe contact between chickens and carrier animals. In Indonesia P. multocida has been isolated from sudden deathlaying hens and broilers. InAceh province incidence of cholera in poultry broiler farms and chicken is quite high, the rate of morbidity and mortality are high.____________________________________________________________________________________________________________________Key words: chicken, fowl cholera, Pasteurella multocida